Vitreoretinal Traction Syndrome, Nitrituria and Human Epidermal Growth Factor Receptor Negative Might Occur in the Aromatase-Inhibitor Anastrozole Treatment - Jie Li; Bin Zhao; YongQing Zhu; Jibiao Wu (International Journal of Clinical Practice)
Background. Anastrozole has been approved for treatment of hormone receptor-positive advanced or metastatic breast cancer by FDA. This study was to assess Anastrozole-related adverse events (AEs) of real-world through data mining of the US Food and drug administration adverse event reporting system (FAERS). Methods. Four different disproportionality analyses, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN) and the multiitem gamma Poisson shrinker (MGPS) algorithms were employed to quantify the signals of Anastrozole-associated AEs. Results. A total 25 system organ class (SOCs) and 300 significant disproportionality Preferred Terms (PTs) were found in this study. The top 5 most significant SOCs were Eye disorders, renal and urinary disorders, respiratory, thoracic and mediastinal disorders, investigations, and cardiac disorders. Unexpected significant AEs was vitreoretinal traction syndrome (ROR = 1108.22, PRR = 1103.98, IC025 = 9.51, EBGM05 = 389.98), nitrituria (ROR = 3561.82, PRR = 3557.28, IC025 = 10.38, EBGM05 = 318.83) and human epidermal growth factor receptor negative (ROR = 675.04, PRR = 674.01, IC025 = 9, EBGM05 = 204.57). Conclusion. The Unexpected significant AEs associated with anastrozole were identified in this study, warrants urgent clarification through additional prospective studies.